2022
DOI: 10.1186/s12544-022-00566-x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic interaction between COVID-19 and shipping freight rates: a quantile on quantile analysis

Abstract: This study determines the impact of the coronavirus disease (COVID-19) that has been prevalent since the year 2019, on the shipping freights. This task has been undertaken by using the wavelet quantile on the quantile approach. The results of the study affirm that the pandemic has in fact affected the shipping freight costs, primarily due to the lower demand for energy and raw materials, and the unavailability of the vessels. In addition to this, the spread of COVID-19 has had a positive impact on the Baltic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Additional influential factors, such as shipping reliability and quality of service (Holguín-Veras et al, 2021), should be accounted for in the model if available from more recent data sources. In addition, the current analysis is based on the 2017 data, and the prevalence of freight modes is constantly changing, especially due to the COVID-19 disruptions on road, air, and rail freight transportation (Borca et al, 2021;Khan et al, 2022). The freight mode choice model will be revisited and updated if more recent data and additional attributes become available.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Additional influential factors, such as shipping reliability and quality of service (Holguín-Veras et al, 2021), should be accounted for in the model if available from more recent data sources. In addition, the current analysis is based on the 2017 data, and the prevalence of freight modes is constantly changing, especially due to the COVID-19 disruptions on road, air, and rail freight transportation (Borca et al, 2021;Khan et al, 2022). The freight mode choice model will be revisited and updated if more recent data and additional attributes become available.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The array of studies on tanker freight rate volatility represents a vital component of maritime economics, with ramifications extending into the broader global economy [30][31][32][33][34]. These time series analyses delve into the interplay between numerous variables affecting freight rates, such as crude oil prices, charter rates, fleet size, and policy changes, aiming to enhance forecasting models and risk management practices within the shipping industry [35][36][37][38][39][40]. Multifractal analysis has emerged as a new trend in these studies,gaining traction due to its ability to capture the asymmetric nature of market risks, demonstrating different magnitudes of response to upward and downward trends and uncovers various scaling behaviors within the data [41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Sea freight rates increased around ten times higher from pre-pandemic lows (from 2019 to early 2020) to the worst time in 2021, its autumn (e.g., Freightos FBX index in containers, and Baltic Dry Index in bulk shipping; e.g., Rao and Saul 2021;Investing.com 2022). Research has confirmed that these extreme price changes were tied to the pandemic time and its numerous restrictions and lockdowns (Rožić et al 2022;Khan et al 2022). Purchasing of components also became increasingly more costly, and availability concerns were high.…”
Section: Introductionmentioning
confidence: 99%